The Coast Guard’s Next Decade: An Assessment of Emerging Challenges and Statutory Needs - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
In the face of climate change, technological innovation, and global strategic competition, the U.S. Coast Guard will need to respond to many developments in the maritime domain over the next decade. The Coast Guard likely has sufficient statutory authority to respond to most of these developments, but some developments may call for new or clarified statutory authority as well as coordination with international bodies. Current statutory manning requirements, for example, will limit the Coast Guard’s ability to authorize the regulated use of uncrewed vessels with autonomous systems. New authority may also be needed to establish spaceflight-related safety zones applicable to foreign-flagged vessels within 200 nautical miles of the U.S. coastlines.These are among the findings in TRB Special Report 346: The Coast Guard’s Next Decade: An Assessment of Emerging Challenges and Statutory Needs from the Transportation Research Board of the National Academy of Sciences, Engineering, and Medicine.The report emphasizes that in addition statutory authority, the Coast Guard will need key organizational and operational capabilities, including a well-trained workforce, to respond to future challenges. A short video charts the Coast Guard's next decade.
Keywords: Transportation and Infrastructure

Thought Leader Forum Summary—Emerging Issues for ACRP - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
TRB’s Airport Cooperative Research Program (ACRP) Research Results Digest 28: Thought Leader Forum Summary—Emerging Issues for ACRP summarizes a January 30, 2019, forum to identify the most important issues facing the airport industry within the next 5 to 10 years.The goal of this exercise was to engage the ACRP’s Airport Operations Committee (AOC) directly with other thought leaders in the industry to identify and define high-level emerging critical issues that impact, or will soon impact, the airport industry.The digest describes the results of a pre-Forum survey designed to help shape the Forum discussion, summarizes the results of the forum itself, and explores potential next steps.
Keywords: Transportation and Infrastructure

Emerging Technologies Applicable to Hazardous Materials Transportation Safety and Security - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2011)
TRB’s Hazardous Materials Cooperative Research Program (HMCRP) Report 4: Emerging Technologies Applicable to Hazardous Materials Transportation Safety and Security explores near-term (less than 5 years) and longer-term (5–10 years) technologies that are candidates for enhancing the safety and security of hazardous materials transportation for use by shippers, carriers, emergency responders, or government regulatory and enforcement agencies.The report examines emerging generic technologies that hold promise of being introduced during these near- and longer-term spans. It also highlights potential impediments (e.g., technical, economic, legal, and institutional) to, and opportunities for, their development, deployment, and maintenance.The research focused on all modes used to transport hazardous materials (trucking, rail, marine, air, and pipeline) and resulted in the identification of nine highly promising emerging technologies.
Keywords: Transportation and Infrastructure

Private Transit: Existing Services and Emerging Directions - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
TRB's Transit Cooperative Research Program (TCRP) Research Report 196: Private Transit: Existing Services and Emerging Directions provides information about private transit services and ways they are addressing transportation needs in a variety of operating environments. The document contains an overview and taxonomy of private transit services in the United States, a review of their present scope and operating characteristics, and a discussion of ways they may affect the communities in which they operate along with several case studies and other supporting information.Private transit services—including airport shuttles, shared taxis, private commuter buses, dollar vans and jitneys—have operated for decades in many American cities. Recently, business innovations and technological advances that allow real-time ride-hailing, routing, tracking, and payment have ushered in a new generation of private transit options. These include new types of public-private partnership that are helping to bridge first/last mile gaps in suburban areas.The report also examines ways that private transit services are interacting with communities and transit agencies, as well as resulting impacts and benefits.
Keywords: Transportation and Infrastructure

Emerging Technologies for Construction Delivery - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2007)
TRB’s National Cooperative Highway Research Program (NCHRP) Synthesis 372: Emerging Technologies for Construction Delivery explores the use of five emerging technologies for transportation construction projects: global positioning systems for layout, machine guidance, and quantity tracking; handheld computers for construction records; automated temperature tracking for concrete maturity monitoring; four-dimensional computer-aided drafting modeling for constructability analysis and improved communications; and web-based video cameras for remote project monitoring.
Keywords: Transportation and Infrastructure

Current and Emerging Issues Facing the Airport Industry - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2009)
TRB’s Airport Cooperative Research Program (ACRP) Research Results Digest 5: Current and Emerging Issues Facing the Airport Industry summarizes the program and the process for identifying strategic research areas for use with the FY 2010 ACRP problem statement solicitation process and beyond.In January 2014 RRD 5 was updated with the release of ACRP RRD 20: Taking Inventory of ACRP Research and the Net Challenges Facing the Airport Industry.
Keywords: Transportation and Infrastructure

Transportation Implications of Emerging Economic Development Trends - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2008)
TRB’s National Cooperative Highway Research Program (NCHRP) Research Results Digest 327: Transportation Implications of Emerging Economic Development Trends explores economic development trends and how transportation relates to these trends. The report focuses on business production, inventory, and logistics and distribution trends and practices; site selection research and practices; labor market considerations; urban and rural development practices; and international trade and global market trends and implications.
Keywords: Transportation and Infrastructure

Improving Public Transportation Technology Implementations and Anticipating Emerging Technologies - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2007)
TRB’s Transit Cooperative Research Program (TCRP) Report 84, e-Transit: Electronic Business Strategies for Public Transportation Volume 8, Improving Public Transportation Technology Implementations and Anticipating Emerging Technologies explores the value of current technologies used in public transportation, examines methods for improving the success of technology implementation, and reviews five promising emerging technologies with application for transit agencies.The declining costs of communications, data storage, and data retrieval are accelerating the opportunities spawned by the Internet and other information and communications technologies. Choosing and sequencing investments in technologies, processes, and people to reduce costs and increase productivity present challenges to the transit manager, who must weigh the costs, benefits, and risks of changing the ways services are delivered. To assist in meeting such challenges, the TCRP Report 84: e-Transit: Electronic Business Strategies for Public Transportation series documents principles, techniques, and strategies that are used in electronic business for public transportation.Appendices for TCRP Report 84, Volume 8 include the following:* Appendix A: Summary of the Transit Agency Leader Focus Group* Appendix B: Summary of the ITS America 2005 Transit GM Summit
Keywords: Transportation and Infrastructure

Naval Engineering in the 21st Century: The Science and Technology Foundation for Future Naval Fleets -- Special Report 306 - Transportation Research Board (The National Academies Press, 2011)
TRB Special Report 306: Naval Engineering in the 21st Century: The Science and Technology Foundation for Future Naval Fleets examines the state of basic and applied research in the scientific fields that support naval engineering and explores whether Office of Naval Research (ONR) activities, under its National Naval Responsibility for Naval Engineering (NNR-NE) initiative, have been effective in sustaining these fields. The committee developed a series of conclusions and recommendations in five areas--the value of the NNR-NE, the state of science and technology supporting naval engineering, the wholeness of the NNR-NE research portfolio, opportunities for enhancement of research and education, and the effectiveness of the NNR-NE initiative. The report's recommendations are addressed to the administrators of the NNR-NE initiative and of ONR.
Keywords: Engineering and Technology

Energy and Transportation: Challenges for the Chemical Sciences in the 21st Century - National Research Council (The National Academies Press, 2003)
This book, also based on a workshop, assesses the current state of chemistry and chemical engineering at the interface with novel and existing forms of energy and transportation systems. The book also identifies challenges for the chemical sciences in helping to meet the increased demand for more energy, and opportunities for research in energy technologies and in the development of transportation vehicles.
Keywords: Transportation and Infrastructure; Math, Chemistry, and Physics

Preventing Teen Motor Crashes: Contributions from the Behavioral and Social Sciences: Workshop Report - Institute of Medicine; Transportation Research Board; National Research Council (The National Academies Press, 2007)
From a public health perspective, motor vehicle crashes are among the most serious problems facing teenagers. Even after more than six months of being licensed to drive alone, teens are two to three times more likely to be in a fatal crash than are the more experienced drivers. Crash rates are significantly higher for male drivers, and young people in the United States are at greater risk of dying or being injured in an automobile than their peers around the world. In fact, in 2003 motor vehicle crashes was the leading cause of death for youth ages 16-20 in the United States. Understanding how and why teen motor vehicle crashes happen is key to developing countermeasures to reduce their number. Applying this understanding to the development of prevention strategies holds significant promise for improving safety but many of these efforts are thwarted by a lack of evidence as to which prevention strategies are most effective. Preventing Teen Motor Crashes presents data from a multidisciplinary group that shared information on emerging technology for studying, monitoring, and controlling driving behavior. The book provides an overview of the factual information that was presented, as well as the insights that emerged about the role researchers can play in reducing and preventing teen motor crashes.
Keywords: Transportation and Infrastructure; Behavioral and Social Sciences; Health and Medicine

Urban Air Mobility: An Airport Perspective - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Urban Air Mobility (UAM), or its generalized version, Advanced Air Mobility (AAM), is an emerging aerial transportation approach that involves the operation of highly automated aircraft for a safe and efficient system to transport passengers or cargo at lower altitudes of airspace within urban, suburban, and exurban areas. UAM initiatives are advancing in many communities and will likely bring many societal changes.The TRB Airport Cooperative Research Program's ACRP Research Report 243: Urban Air Mobility: An Airport Perspective provides a comprehensive examination of the emerging UAM industry, with a particular focus on its impacts and opportunities for airports.Supplemental to the report are an Airport AAM Preparation Checklist and a UAM Airport Assessment Toolkit.
Keywords: Transportation and Infrastructure

State Transportation Agency Decision-Making for System Performance: Conduct of Research Report - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Transportation agencies must grapple with a broad range of trends and issues that influence and act upon the systems they manage and operate. Issues include climate change, goods movement, changing centers of population and economic activity, and telework, among others.NCHRP Web-Only Document 345: State Transportation Agency Decision-Making for System Performance: Conduct of Research Report, from TRB's National Cooperative Highway Research Program, depicts the relationships among trends, issues, and system objectives.The report is supplemental to NCHRP Research Report 1042: State Transportation Agency Decision-Making for System Performance: Practitioner’s Playbook.
Keywords: Transportation and Infrastructure

Technology and Economic Analysis in the Prepublication Version of the Report 'Effectiveness and Impact of Corporate Average Fuel Economy (CAFE) Standards': Letter Report - Transportation Research Board (The National Academies Press, 2002)

Integrating Freight Movement into Twenty-First-Century Communities' Land Use, Design, and Transportation Systems - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Public sector planners and officials desire a clearer understanding of how goods movement benefits communities through job creation, tax revenues, and other benefits, while balancing the potential environmental and/or community disbenefits.NCHRP Web-Only Document 373: Integrating Freight Movement into Twenty-First-Century Communities' Land Use, Design, and Transportation Systems, from TRB's National Cooperative Highway Research Program, develops a planning toolkit for public-sector decision-makers to better integrate freight and goods movement into the planning process for land use, design, and multimodal transportation systems.Supplemental to the report is a Freight Planning Toolkit that consists of instructional white papers to assist transportation planners in linking freight and land use. The topics include (1) stakeholder engagement, (2) freight livability, (3) freight logistics decision-making, (4) emerging trends, (5) data, and (6) freight and land use. In addition, there is an Excel-based tool that will assist the user in identifying resources specific to their context.
Keywords: Transportation and Infrastructure

The Challenge of Providing Future Infrastructure in an Environment of Limited Resources, New Technologies, and Changing Social Paradigms: Proceedings of a Colloquium, March 24, 1995 (The National Academies Press, 1995)

Vessel Navigation and Traffic Services for Safe and Efficient Ports and Waterways: Interim Report (The National Academies Press, 1996)

Nondestructive Evaluation of Highway System Asset Foundational Condition and Capability - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
A more efficient and strategic approach is needed for managing transportation assets, in general, and, in particular, their foundational elements during their service life. This need is exacerbated by uncertainties in the impact of changes to the aging transportation infrastructure assets caused by continued degradation, climate change, unreliable funding, effects of international trade, and possible changes in national policies and priorities—all in the context of almost no information on the condition and service capability of the foundation elements.The TRB National Cooperative Highway Research Program's NCHRP Research Report 1041: Nondestructive Evaluation of Highway System Asset Foundational Condition and Capability provides a critical review of current and leading practices, research, and applications of emerging and new nondestructive technologies, and identifies the potential for further advancements to near-term opportunities for improving agencies’ capabilities to assess and monitor the foundational integrity, condition, and service capability of highway system assets.
Keywords: Transportation and Infrastructure

Measuring and Managing Fare Evasion - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Fare evasion is generally defined as a passenger using public transit without paying the required fare or possessing the required fare media or valid proof of fare payment. Fare evasion has significant implications for the financial sustainability of transit systems and must be replaced by another stable source of funding.The TRB Transit Cooperative Research Program TCRP Research Report 234: Measuring and Managing Fare Evasion explores in detail the recent past and emerging future of fare enforcement on transit systems.
Keywords: Transportation and Infrastructure

State Transportation Agency Decision-Making for System Performance: Practitioner’s Playbook - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Transportation agencies need to identify and evaluate current and emerging performance measures, analytic tools, and data sources in order to improve their ability to integrate issues such as climate change, goods movement, changing centers of population and economic activity, and telework into their decisions about system performance.NCHRP Research Report 1042: State Transportation Agency Decision-Making for System Performance: Practitioner’s Playbook, from TRB's National Cooperative Highway Research Program, presents an analytic framework for transportation agencies to employ to improve their ability to integrate critical issues into their decisions about making transportation safe, efficient, sustainable, and equitable for people and goods.Supplemental to the report are NCHRP Web-Only Document 345: State Transportation Agency Decision-Making for System Performance: Conduct of Research Report; a Visualization Tool that depicts the relationships among trends, issues, and system objectives; a guide to using the tool; and a technical memorandum.Accessing the Visualization Tool: After clicking on the link above, download the tool and extract the files. Open “homepage.html” to begin using the tool.Software disclaimer: Any software included is offered as is, without warranty or promise of support of any kind either expressed or implied. Under no circumstance will the National Academy of Sciences or the Transportation Research Board (collectively “TRB”) be liable for any loss or damage caused by the installation or operation of this product. TRB makes no representation or warranty of any kind, expressed or implied, in fact or in law, including without limitation, the warranty of merchantability or the warranty of fitness for a particular purpose, and shall not in any case be liable for any consequential or special damages.
Keywords: Transportation and Infrastructure